ANALISIS PEMASARAN CENGKEH DI KECAMATAN BAOLAN KABUPATEN TOLITOLI - Hanapi, Hariani; Anwar, Chairil; Damayanti, Lien (Katalogis, 2021)
This research aims to find out the channels, margins, and efficiency of marketing. Baolan Subdistrict was chosen purposively because this area has the highest harvested area and production in Tolitoli District. The research sample was52 farmers and 4 traders consisting of two village traders, one Subdistrict traders, and one District trader.The analysis model used is the channel, margin, andefficiency of marketing. The results of the research show that there are three clove marketing channels in Baolan Subdistrict, Tolitoli District.The total marketing margin obtained on channel three is IDR. 4.903, while the total margin on channel one is IDR. 4.865 and the total margin on channel two are IDR. 4.353. The efficiency of clove marketing obtained on three marketing channelsis less than 0.01 percent, and the efficiencymarketing channel is channel three.